A biological control approach to reducing Naupactus godmani (Curculionidae) populations in citrus using entomopathogenic nematodes. (January 2019) - Gulcu, Baris; Hodson, Amanda; Omaleki, Vinton; Ross, Andrew B.; Lewis, Edwin E.
Abstract: The presence of eggs of the Fuller rose beetle, Naupactus godmani (Coleoptera: Curculionidae), on fruits are an issue for export of California navel oranges. In an effort to develop a management strategy for this pest, we tested three entomopathogenic nematode species in laboratory, greenhouse and field trials. Steinernema carpocapsae killed all Fuller Rose Beetle adults in laboratory assays, but were unsuccessful in the greenhouse. In field trials, applications of Steinernema riobrave reduced the number of emerging adults caught in Tedder's traps compared to Heterorhabditis bacteriophora and controls. Trees where the soil around the bases were treated with Grub Guard (a product containing, H. bacteriophora and S. carpocapsae ) leaf damage caused by adults was 44% less compared to controls. Entomopathogenic nematodes used as a sole method of FRB management are unlikely to provide satisfactory results in the field. Combining entomopathogenic nematodes with other biopesticides may be the best approach to their management. Highlights: Fuller Rose Beetle (FRB) is a problem at navel orange in California, US. Steinernema riobrave reduced the number of emerging adults in field applications. Grub Guard decreased 44% less leaf damage compared to controls. Entomopathogenic nematodes can be a good option at integrated management of FRB.